Washing Methods and Filtration on the Extraction of Durian Peel Pectin - Karen Darmawan; Rona Joharmi Nainggolan; Lasma Nora Limbong (Universitas Sumatera Utara, 2014)
This research was aimed to know the washing methods and filtration thickness on the quality of pectin extracted from durian peel and to increase economic value on durian peel waste. This research was conducted using a completely randomized design with two factors, namely the washing methods; washed and unwashed with alcohol and filtration thickness: 1 piece, 2 pieces, 3 pieces, 4 pieces, 5 pieces, and 6 pieces. The parameters analyzed were yield, water content, ash content, equivalent weight, methoxyl content, galacturonic content and color. The results showed that the washing methods had highly significant effect on yield, water content, and colors and had significant effect on ash content and provided no effect on equivalent weight, methoxyl content, galacturonic content. Filtration thickness gave highly significant effect on yield, water content, ash content, equivalent weight, methoxyl content and galacturonic content. Interactions of the two factors gave highly significant effect on yield and color and had significant effect on ash content and provided no effect on water content, equivalent weight, methoxyl content and galacturonic content. Washing with alcohol and filtration thickness of 6 pieces produce the best quality of durian peel pectin. Keywords: durian peel, filtration thickness, pectin, washing methods.